Qualitative Research on Status Analysis and Psychological Intervention Strategy of Elementary Students’ School Weariness - Alhashedi, Sena; Jun, Sun Xiao; Alfalahi, Abdullah (International Journal For Research In Educational Studies, 2019)
According to the contrastive analysis of students’ school performance in recent years, it has significantly observed the following points including the quality reduction of student sourceyears by years, decrease of student’s enthusiasm for study and school weariness prevailing among student group, all of which has brought serious effect on the teaching quality of schools. On this occasion, how to solve the problem of elementary student’s school weariness requires no delay. To solve the problem of school weariness at its root, we should and must make an in-depth study on the current situation, type, reason and intervention strategies of elementary student’s school weariness. Furthermore, it is also necessary for us to conduct specific qualitative studies on the all reasons of possible pressures. By focusing on associated items, I would like to have further understanding of students’ subjective consciousness and personal feeling by interview as research method and get preparation for better guidance of overcoming student’s school weariness in the future. This paper comes up with relevant intervention strategies on psychological features of vocational high school students’ school weariness in combination with the theories of psychology, especially affective strategies commonly used in applied educational psychology, to make psychological counseling for elementary students’ school weariness, which allows the teachers of vocational high school to solve the psychological problems of students’ school weariness during their educational practice in a more scientific and effective way under the guidance of theory.